2015
DOI: 10.3109/02699052.2015.1060358
|View full text |Cite
|
Sign up to set email alerts
|

Does anticholinergics drug burden relate to global neuro-disability outcome measures and length of hospital stay?

Abstract: Primary Objective: To assess the relationship between disability, length of stay (LOS) and anticholinergic burden (ACB) with people following acquired brain or spinal cord injury.Research Design: A retrospective case note review assessed total rehabilitation unit admission. Conclusions: There was a statistically significant correlation of ACB and neuro-disability measures and LOS amongst this patient cohort. Methods4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Despite our results indicated that those on antipsychotic medications on admission were significantly more likely to experience post-operative delirium, there was insufficient data to identify a potential association with anticholinergic medications, such as benzodiazepine. Anticholinergics have been associated with cognitive impairment (Fox et al, 2014), reduced functional recovery (Sakel et al, 2015) and increased incident delirium in non-surgical elderly cohorts (Naja et al, 2016). Siddiqi et al (2016) reported that there remains no clear evidence as to whether cholinesterase inhibitors or antipsychotic medications reduce incident delirium when used peri-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our results indicated that those on antipsychotic medications on admission were significantly more likely to experience post-operative delirium, there was insufficient data to identify a potential association with anticholinergic medications, such as benzodiazepine. Anticholinergics have been associated with cognitive impairment (Fox et al, 2014), reduced functional recovery (Sakel et al, 2015) and increased incident delirium in non-surgical elderly cohorts (Naja et al, 2016). Siddiqi et al (2016) reported that there remains no clear evidence as to whether cholinesterase inhibitors or antipsychotic medications reduce incident delirium when used peri-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, many factors that contribute to the development of MCI after SCI [11]. These may include functional changes to the cardiovascular [38][39][40] and autonomic nervous system [41], psychological changes such as mood disturbances [42], medications [43][44][45], ageing [14,[46][47][48], sleep disorder [49,50], fatigue [8], and social changes, such as the potential for decreased social participation [51,52]. Some of these risks (e.g., depression, polypharmacy) are transient, while others (e.g., brain injury, cardiovascular dysfunction) contribute to degenerative or long-term courses of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Krebs et al [43] found no relationship between antimuscarinic treatment of neurogenic lower urinary tract dysfunction and subsequent performance on neuropsychological testing after a treatment-period of 3 months. Two studies independently exploring the effects of anticholinergic burden and gabapentin on cognition found limited evidence of adverse reactions relating to the use of these medications in patients with SCI [44,45]. These results are in contrast to a sizable body of evidence of negative associations between anticholinergic medication-use and cognitive impairment in able-bodied individuals [62][63][64][65][66] and individuals comprising other illness samples [67][68][69][70][71], and may relate to inadequate length of follow-up, insufficient statistical power to detect effects, and/or use of measures that lack sensitivity to detect cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, just a few studies investigated its association with mortality, showing that it might predict such an outcome in the general population and in community‐dwelling and institutionalized older people . However, evidence about the ACB score among hospitalized patients is limited to the demonstration of its impact on cognitive performance and length of stay, whereas no studies investigated the impact of ACB score on mortality among older patients discharged from hospital, which represent a particularly frail and vulnerable population …”
Section: Introductionmentioning
confidence: 99%
“…9 However, evidence about the ACB score among hospitalized patients is limited to the demonstration of its impact on cognitive performance and length of stay, whereas no studies investigated the impact of ACB score on mortality among older patients discharged from hospital, which represent a particularly frail and vulnerable population. 15,17 Therefore, we aimed to investigate the relationship between the ACB score and 1-year mortality in patients discharged from acute care hospitals. Additionally, we also aimed at investigating the impact of cognitive impairment and history of falls, that is, two markers of frailty that could represent important effect modifiers, on the relationship between ACB and mortality.…”
Section: Introductionmentioning
confidence: 99%